A gradient of glycolytic activity coordinates FGF and Wnt signaling during elongation of the body axis in amniote embryos - Oginuma, Masayuki (Dev Cell, 2017)
Mammalian embryos transiently exhibit aerobic glycolysis (Warburg effect), a metabolic adaptation also observed in cancer cells. The role of this particular type of metabolism during vertebrate organogenesis is currently unknown. Here, we provide evidence for spatiotemporal regulation of glycolysis in the posterior region of mouse and chicken embryos. We show that a posterior glycolytic gradient is established in response to graded transcription of glycolytic enzymes downstream of FGF signaling. We demonstrate that glycolysis controls posterior elongation of the embryonic axis by regulating cell motility in the presomitic mesoderm and by controlling specification of the paraxial mesoderm fate in the tail bud. Our results suggest that glycolysis in the tail bud coordinates Wnt and FGF signaling to promote elongation of the embryonic axis.